PEMANFAATAN DAUN KELOR SEBAGAI CAMPURAN OLAHAN MAKANAN DAN MENGANTISIPASI VIRUS COVID-19 - lubis, sitirahmadani; M. ALIF ALFARUQI,; Aan Kriswana Fasha,; Manurung, Nurul Intan (JURNAL AGRIBISAINS, 2021)
Moringa leaves can be processed in various food and beverage products such as clear vegetables, juice, omelette, chips, nastar, donuts, bakwan and Moringa leaf noodles. In addition, Moringa leaves can be processed as herbal froods. Currently, with the covid-19 pandemic conditions around the world, many alternative herbal ingredients are consumed by the public to increase body nutrition in order to prevent transmission of the virus, one of which is Moringa leaves. Moringa plants are high in nutrients, such as vitamin C, calcium, vitamin A, potassium, and protein. The purpose of implementing this KKN activity is to provide information and, to provide assistance to the community in utilizing Moringa plants to prevent Covid-19, as well as to improve community skills in making Moringa herbal food to prevent Covid-19. This KKN was held at the in Air Joman Village, with a series of activities including the socialization of the importance of Moringa leaves, the preparation of raw materials for making herbal moringa foods, and the practice of manufacturing Moringa leaf herbal food products. The results of this activity were the socialization of the use of Moringa leaves as a way to increase immunity in order to prevent viruses and the practice of making Moringa leaf tea with village head, students and lecturers at Air Joman Village. Keywords: herbal food; moringa leaves; prevents covid-19